2023
DOI: 10.24875/bmhime.m18000019
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of transgender children and adolescents

Abstract: Transgender or gender incongruence (GI) persons identify themselves with a gender that is different from that correspondent to their birth sex. The demand for health services by families with transgender children or adolescents tends to increase. The prevalence of GI in children is unknown; however, it has been estimated to be > 1% in adolescents. Transgender persons are at increased risk of depression, suicide, illicit drug abuse, human immunodeficiency virus infection, and non-accidental injuries. The most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The signal characteristics of rat CBT exhibit remarkable similarities to human peripheral temperature (See: Sanchez-Alavez et al, 2011 ; Shechter et al, 2011 ; Grant et al, 2020b ). Monitoring human peripheral temperature during adolescence could serve broad purposes – from personalizing health education based on self-collected data ( Eschler et al, 2019 ; Fowler et al, 2020 ), to adapting teaching style to an individual’s developmental phase ( Davidow et al, 2016 ; DePasque and Galván, 2017 ; Piekarski et al, 2017 ; Master et al, 2020 ), to enabling research into the impact of teen contraceptive use ( Martinez, 2015 ; Patseadou and Michala, 2017 ) or the process of gender transition ( Castilla-Peón, 2018 ; Strittmatter and Holtmann, 2020 ). Together, pubertal monitoring via continuous body temperature is worthy of further investigation in both animal models and human subject populations for its potential utility to individuals, researchers, families, and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The signal characteristics of rat CBT exhibit remarkable similarities to human peripheral temperature (See: Sanchez-Alavez et al, 2011 ; Shechter et al, 2011 ; Grant et al, 2020b ). Monitoring human peripheral temperature during adolescence could serve broad purposes – from personalizing health education based on self-collected data ( Eschler et al, 2019 ; Fowler et al, 2020 ), to adapting teaching style to an individual’s developmental phase ( Davidow et al, 2016 ; DePasque and Galván, 2017 ; Piekarski et al, 2017 ; Master et al, 2020 ), to enabling research into the impact of teen contraceptive use ( Martinez, 2015 ; Patseadou and Michala, 2017 ) or the process of gender transition ( Castilla-Peón, 2018 ; Strittmatter and Holtmann, 2020 ). Together, pubertal monitoring via continuous body temperature is worthy of further investigation in both animal models and human subject populations for its potential utility to individuals, researchers, families, and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The signal characteristics of rat CBT exhibit remarkable similarities to human peripheral temperature (See:(61,148,187)). Monitoring human peripheral temperature during adolescence could serve broad purposes – from personalizing health education based on self-collected data(188, 189), to adapting teaching style to an individual’s developmental phase(190193), to enabling research into the impact of teen contraceptive use(194, 195) or the process of gender transition(196, 197). Together, pubertal monitoring via continuous body temperature is worthy of further investigation in both animal models and human subject populations for its potential utility to individuals, researchers, families, and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…(3,63) These individuals maybe two times more likely to use cocaine, inhalants, or amphetamines, three times more likely to use tobacco at school, and two times more likely to abuse pain medications. (42) It is also noted that these adolescents are at risk for early alcohol consumption and early initiation of sexual intercourse from two to three times greater than cisgender adolescents (44,63), and also have a greater risk of developing overweight and obesity. (27,63) It was observed that transgenders aged between 6 and 23 years had a psychosocial health level significantly lower than cisgenders, and similar to that of (remove) young people with cerebral palsy.…”
Section: Mental Health and Self-perception Overviewmentioning
confidence: 99%
“…The gender transition process associated with hormonal therapy with or without surgical intervention has been effective in decreasing suicide attempts, improving gender dysphoria and the quality of life of these individuals. (44) The study by Edwards-Leeper and Spack, demonstrates that biological boys seek medical intervention earlier than biological girls. Pubertal suppression can prevent emotional and psychological distress, in addition to allowing the clinician to assess how the teenager works when unwanted secondary sexual characteristics are suppressed.…”
Section: Puberal Suppression / Medical Interventionmentioning
confidence: 99%